10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
There is a global syndemic of HIV, mental health challenges, substance use, and structural barriers. Critical to local HIV prevention efforts is understanding this syndemic in the context of rising stimulant use to inform intervention development. Adhering to the EPIS model, we conducted 32 in-depth individual qualitative interviews with people who use stimulants and have unmet structural needs to (1) identify barriers/facilitators of HIV prevention and (2) get feedback on evidence-based intervention content (e.g., emotion- and problem-focused coping skills) to address identified barriers. Thematic content analysis was applied. The sample had a mean age of 48 years (standard deviation = 10.8), with 46.9% identifying as men, 62.5% as White, and 50.0% as having ≤high school diploma/GED (general educational development). Multi-level barriers/facilitators of HIV prevention included knowledge, motivation (individual), provider relationships (interpersonal), access, and cost (institutional/structural). Skills to cope with psychosocial distress and problem-solve barriers to getting social services were perceived to be helpful. A psycho-behavioral intervention would best be implemented as part of syndemic-focused programming that also includes contingency management for HIV prevention behaviors and stimulant use, social activities not centered on drug use, and case management. This study advances HIV prevention by informing psycho-behavioral intervention development that is person-centered and focused on sustainable implementation.